ENHANCEMENT OF EXCLUSIVE COMPETENCIES OF FOREIGN STUDENTS BY TEACHING THE HISTORY OF MEDICINE IN MEDICAL EDUCATION (World Bulletin of Social Sciences, 2024)
In this article, the aspect of the formation of the exclusive competence of the foreign student in Uzbekistan through the Connect-Extend-Challenge model of teaching the history of medicine is shown, and it is reflected that the teaching of the history of medicine through this model plays an important role in the full formation of the exclusive competence in the future student working in medical education
Keywords: competence; cognitive activity; pedagogical creativity; didactic possibility